USER USER EXPERIENCE TEST MARKETPLACE E-COMMERCE KOPI DENGAN MENGGUNAKAN ISO METRICS PADA UMKM DI ACEH TENGAH - Desvina Yulisda; Rahma Fitria; Eka Susanti; Ebi Putra (Jurnal Informatika Kaputama (JIK), 2023)
E-commerce sites have become popular for sellers in promoting their business during the covid-19 pandemic. One of the e-commerce that is used in promoting business is shopee. . This e-commerce website is very often used by Indonesian people in selling goods. In order to make it easier for middle-range businesss to market their products on e-commerce shopee, this website needs to be tested by users to provide feedback on how the website feels after use. The purpose of this research is to test the user experience (UX) on e-commerce shopee as a seller. The UX test was carried out in a room set-up like in a laboratory with 10 users who have never used the Shopee website as sellers. During testing, users are given several tasks related to the website while the facilitator makes observations to analyze usability metrics. The data collected will reveal the weaknesses and strengths of the website. Usability score is measured based on ISO usability metrics including effectiveness, efficiency and satisfaction. The results of this UX test show that the website is quite user-friendly as evidenced by a usability score of around 84% or above average. It is expected that this research can be adopted by software engineers or usability testers to produce user-friendly e-commerce that makes users comfortable and easy to use the website.